Analisis Strategi Pemasaran Produk Pembiayaan Kepemilikan Emas Dalam Meningkatkan Jumlah Nasabah - Asmawarna Sinaga; Usmaidar; Rezky Dwinda Br Silalahi (Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to analyze the marketing strategy of gold financing products (gold installments) at PT. Bank Syariah Indonesia KCP Pangkalan Brandan. The method used is descriptive qualitative through interviews, observation, and documentation. The results show that the gold installment product with murabahah contracts complies with sharia principles. The marketing mix-based marketing strategy (product, price, place, promotion) was able to increase the number of customers from 116 in 2021 to 425 in 2025. A SWOT analysis confirmed the strengths, weaknesses, opportunities, and threats that influence this strategy. The study concluded that the gold installment marketing strategy is effective, but needs to be strengthened with product innovation, digital promotion, and public education.